Penerapan Senam Ergonomik untuk Menurunkan Tekanan Darah Pada Lansia Hipertensi di UPTD Tuna Rungu Wicara dan Lanjut Usia Kota Pematangsiantar - Vany Debora Tampubolon; Nabilah Siregar (SEHATI: Jurnal Kesehatan, 2024)
Hypertension is called the silent killer, where the elderly are at the highest risk of developing hypertension. This study aims to reduce blood pressure in elderly people with hypertension. The design of this research is descriptive using a case study method on 2 hypertensive clients at the UPTD for the Deaf, Speech Impaired and Elderly in Pematangsiantar, with a purposive sampling technique. Data was collected using interview techniques, observation, and physical examinations carried out using a gerontic perspective assessment format. The results of the research showed that blood pressure in both clients decreased, namely blood pressure from 170/100 mmHg down to 140/80 mmHg in client I, and 160/90 mmHg down to 130/80 mmHg in clien II after doing ergonomic exercises for three days. The author suggests that ergonomic exercises can be applied routinely to elderly people with hypertension.